Геоинформационная система магматических, метаморфических и рудных формаций Республики Армения - А. А. Авакян; Р. Л. Мелконян; А. М. Манандян (ՀՀ ԳԱԱ հրատ.)
В данной статье изложены принципы модели данных, описывающие магматические, метаморфические и рудные формации, и их интеграции в единую геоинформационную систему (ГИС). Впервые разработана специфическая геологическая модель данных, на основании которой создана ГИС магматических, метаморфических и рудных формаций. Մշակվել և կազմվել է մասնագիտացված երկրաբանական տվյալների մոդել, ինչի հիման վրա ստեղծվել է մագմատիկ, մետամորֆիկ և հանքային ֆորմացիաների աշխարհագրական տեղեկատվական համակարգ (ԱՏՀ)։ ԱՏՀ–ն մշակվել և կիրառվել է է «ՀՀ (Հյուսիսային Հայաստան) մագմատիկ, մետամորֆիկ և հանքային ֆորմացիաների 1:300 000 մասշտաբի քարտեզի» կազմման ընթացքում։ Specialized geological data model has been designed, based on which a GIS of magmatic, metamorphic and ore formations has been developed. The GIS has been developed and used for constructing the “Map of magmatic,metamorphic and ore formations of the Republic of Armenia (Northern Armenia), Scale 1:300 000”. Unified concept, logical, physical and geo-information models of the data of the formations map have been developed, by means of which the main concepts, attributes and their relations by hierarchical schemes have been defined. The GIS functions are based on the structure, relationships within database and additional programs for the querying and searching of spatial and attribute data, generalization and representation of results as reports. The GIS structure and relationships among its components provide an opportunity for is further development by expanding of its analytical functionalities.
Keywords: Science; Geology; Mineralogy